Sensory and physicochemical characteristics of low sodium salami - Marcio Aurelio de Almeida; Nilda Doris Montes Villanueva; Jair Sebastião da Silva Pinto; Erick Saldaña; Carmen J. Contreras-Castillo (Scientia Agricola, 2016)
ABSTRACT The aim of the present study was to develop low sodium salami prepared with pork, low-fat beef and a small quantity of pork back fat (150 g kg−1). Sodium chloride (NaCl) was replaced by potassium chloride (KCl) and calcium chloride (CaCl2), and salamis were tasted to obtain low-salt salami with sensory characteristics similar to those found in commercial ones. Salamis were prepared following seven different treatments. Treatments included five different combinations of KCl and CaCl2 which varied from 5 g kg−1 to 10 g kg−1 and two controls containing high (25 g kg−1) and low (10 g kg−1) concentrations of NaCl. The right level of saltiness of each treatment was evaluated on “just-about-right” (JAR) scales and analyzed by Penalty Analysis. The results showed differences in pH and Aw (water activity) due to NaCl reduction. Salt replacement mixtures of KCl/CaCl2 in salamis did not affect this process technologically (slicing, appearance and texture), and the decrease in Na content was approximately 55 %. Although no significant differences were observed in appearance, treatments differed (p ≤ 0.05) in flavor, texture, and overall liking. As regards salt content of salami, consumers considered treatments with low NaCl content and replacers KCl and CaCl2 (% Na) as having an acceptable level of saltiness. However, this replacement produced a strange taste. Thus, the production of low sodium salamis using salt replacers (KCl and CaCl2) or salamis without replacers with a value higher than 1 % of NaCl can be used effectively without compromising major sensorial attributes.